PEMERTAHAN BAHASA BANJAR DI KECAMATAN PULAU LAUT BARAT - Rahmayanti, Selawati (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2025)
The aims of the research to describe language preservation of the Banjar community in Pulau Laut Barat District. The research method used is qualitative, which is a research method that produces analytical procedures that do not use statistical analysis or other quantitative methods. Based on the results of research, it can be concluded that the language preservation of the Banjar community in Pulau Laut Barat District consists of: a) The efforts of the speakers themselves, which are nothing more than loyalty to their language, with 21 speakers of their own language. The loyalty of speakers is crucial for success in language preservation. b) The efforts of the local community, with the full support of the government, can help a language survive, with 6 speakers for the local community. c) The efforts of parents play a crucial role in language preservation. Consequently, many regions have been able to maintain their languages ​​thanks to the efforts of parents, with 3 speakers. These efforts take the form of teaching the language to their children from generation to generation, and they consistently use Banjarese at home and in their surroundings when communicating. Keywords: Retention, Banjar Language